ESOMAT 2009 - 8th European Symposium on Martensitic Transformations 2009
DOI: 10.1051/esomat/200907005
|View full text |Cite
|
Sign up to set email alerts
|

Seismic retrofit for RC columns by NiTi and NiTiNb SMA wires

Abstract: Abstract. This paper conducted several flexural tests of RC (reinforced concrete) columns retrofitted by SMA (shape memory alloy) wires. The RC columns with lap spliced reinforcements at the base show less ductile behaviour than those with continuous reinforcements. SMA wire jackets can increase the ductility of the RC columns with lap spliced reinforcements and thus this study used the two kinds of SMA wires to retrofit such RC columns; the first one is NiTi SMA wire that remains in martensite at room tempera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…However, their jackets did not increase the peak strengths of the concrete cylinders and, thus, their tests were imperfect. Also, he and his colleagues applied SMA wire jackets for reinforced concrete columns with a lap-splice to increase its seismic performance and showed satisfactory results [8].…”
Section: Introductionmentioning
confidence: 99%
“…However, their jackets did not increase the peak strengths of the concrete cylinders and, thus, their tests were imperfect. Also, he and his colleagues applied SMA wire jackets for reinforced concrete columns with a lap-splice to increase its seismic performance and showed satisfactory results [8].…”
Section: Introductionmentioning
confidence: 99%
“…NiTiNb wire can be used as a reliable source of active stress to reinforce, remediate, and retrofit structures. Several studies have demonstrated the use of NiTiNb spirals to strengthen concrete columns (Andrawes et al, 2010; Chen and Andrawes, 2014, 2017; Choi et al, 2009, 2010b, 2010d, 2011, 2013; Shin and Andrawes, 2010). It was found that (Chen and Andrawes, 2017) the strength of concrete confined with SMA spirals was approximately 51% higher than that of unconfined concrete.…”
Section: Introductionmentioning
confidence: 99%
“…However, bonding failure along the interface between FRP sheet and concrete was a defect limiting its further application (Lu et al, 2015;Quiertant and Clement, 2011;Rahai and Akbarpour, 2014;Zhang et al, 2000Zhang et al, , 2015. The seismic performance of the columns which were retrofitted at plastic hinge region by the prestressed memory alloy wire was studied (Choi et al, 2009). The study results indicated that the RC column with circular section could be confined actively by the prestressed memory alloy wire and the ductility of the column could also be enhanced.…”
Section: Introductionmentioning
confidence: 99%